Pressure injury data in Australian acute care settings: A comparison of three data sets. Issue 3 (6th February 2020) - Team, Victoria; Tuck, Michelle; Reeves, Judy; Way, Margaret; Enticott, Joanne; Evans, Susan; Weller, Carolina D.
Abstract: Hospital‐acquired pressure injuries (HAPIs) represent a serious clinical and economic problem. The cost of treating HAPIs in Australian public hospitals was recently reported at AUS983 million per annum. There are three main sources of data for documenting pressure injury (PI) occurrence in Australian hospitals: incident reporting, medical record coded data, and real‐time surveys of pressure injury. PI data reported at hospital level and to external agencies using these three different sources are variable. This reporting issue leads to inaccurate data interpretation and hinders improvement in accuracy of PI identification and PI prevention. This study involved a comparison of the three different data sources in selected Australian hospitals, to improve the accuracy and comparability of data. Findings from this study provide benchmark areas for improvement in PI documenting and reporting. Better understanding the agreement between the three data sets could lead to a more efficient and effective sharing of data sources.